Hybride und energieeffiziente Antriebe für mobile Arbeitsmaschinen 9. Fachtagung, 28. Februar 2023, Karlsruhe - Wissenschaftlicher Verein für Mobile Arbeitsmaschinen, Marcus Geimer, Christian Kunze (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2023)
This book contains the conference proceedings to the lectures of the 9th symposium on 28th February 2023 in Karlsruhe. The state of research and new developments in the field of drive technology for mobile machines are reported in 12 articles. The conference proceedings are characterized by technical contributions on climate-neutral, efficiency-optimized and electrified drives in a variety of machines. In addition to traction drives, drive systems for performing work tasks are also addressed.